Meta-Analysis: The Effect of Social Support on Medication Treatment Adherence in Tuberculosis Patients - Lily Nabillah; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2022)
Background: Tuberculosis is a disease that can be cured by various methods of treatment. However, tuberculosis treatment is often not carried out properly and completely. The importance of medication adherence as a top priority in the effectiveness of treatment of tuberculosis patients through social support. The purpose of this study was to analyze the effect of social support on medication adherence in tuberculosis patients.Subjects and Method: This meta-analysis study used the PRISMA flowchart guideline with PICO, Population= Tuberculosis patients. Intervention= social support. Comparison= without social support. Outcome= medication adherence. The search process was carried out between 2017 and 2022 using Google Scholar, PubMed, Sci-Hub, and Science Direct databases. The keywords used were "Medication Adherence" OR "Drug Adherence" OR "Adherence" OR " treatment adherence" AND "Tuberculosis" OR "multidrug resistant tuberculosis*" OR "Mycobacterium tuberculosis Infection" AND "Social Support" OR "Social Support System" OR "Psychosocial Support System" OR "Support System". Based on the database, there are 10 articles that fulfill the inclusion criteria. Study analysis was using review manager 5.3 software.Results: There were 10 articles from the continents of Asia and Africa selected in this meta-analysis, the results showed that the presence of social support has the possibility to increase adherence to anti-tuberculosis treatment compared to without social support in tuberculosis patients and it was statistically significant (aOR= 2.10; CI 95%= 1.76 to 2.52; p< 0.001).Conclusion: Tuberculosis patients who have strong social support about tuberculosis adherence are more likely to adhere to anti-tuberculosis treatment.Keywords: tuberculosis, social support, medication adherence, meta-analysis.Correspondence:Lily Nabillah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: lilynabillah09@gmail.com. Mobile: +62 821-1135-6435.Journal of Health Promotion and Behavior (2022), 07(03): 250-261DOI: https://doi.org/10.26911/thejhpb.2022.07.03.07